Vibrio cholerae Phage K139: Complete Genome Sequence and Comparative Genomics of Related Phages - Kapfhammer, Dagmar (American Society for Microbiology, 2002)
In this report, we characterize the complete genome sequence of the temperate phage K139, which morphologically belongs to the Myoviridae phage family (P2 and 186). The prophage genome consists of 33,106 bp, and the overall GC content is 48.9%. Forty-four open reading frames were identified. Homology analysis and motif search were used to assign possible functions for the genes, revealing a close relationship to P2-like phages. By Southern blot screening of a Vibrio cholerae strain collection, two highly K139-related phage sequences were detected in non-O1, non-O139 strains. Combinatorial PCR analysis revealed almost identical genome organizations. One region of variable gene content was identified and sequenced. Additionally, the tail fiber genes were analyzed, leading to the identification of putative host-specific sequence variations. Furthermore, a K139-encoded Dam methyltransferase was characterized.